Pitch anything : an innovative method for presenting, persuading and winning the deal - Klaff, Oren (McGraw-Hill, 2011)
When it comes to delivering a pitch, Oren Klaff has unparalleled credentials. Over the past 13 years, he has used his one-of-a-kind method to raise more than $400 million and now, for the first time, he describes his formula to help you deliver a winning pitch in any business situation.Whether you're selling ideas to investors, pitching a client for new business, or even negotiating for a higher salary, "Pitch Anything" will transform the way you position your ideas.According to Klaff, creating and presenting a great pitch isn't an art it's a simple science. Applying the latest findings in the field of neuroeconomics while sharing eye-opening stories of his method in action, Klaff describes how the brain makes decisions and responds to pitches. With this information, you'll remain in complete control of every stage of the pitch process."Pitch Anything" introduces the exclusive STRONG method of pitching, which can be put to use immediately: Setting the FrameTelling the StoryRevealing the IntrigueOffering the PrizeNailing the HookpointGetting a DecisionOne truly great pitch can improve your career, make you a lot of money and even change your life. Success is dependent on the method you use, not how hard you try. "Better method, more money," Klaff says. "Much better method, much more money." Klaff is the best in the business because his method is much better than anyone else's. And now it's yours.Apply the tactics and strategies outlined in "Pitch Anything" to engage and persuade your audience and you'll have more funding and support than you ever thought possible.